A Macroeconomic Analysis of the Effects of Gender Inequality, Wages, and Public Social Infrastructure: The Case of the UK. Issue 2 (3rd April 2022) - Onaran, Özlem; Oyvat, Cem; Fotopoulou, Eurydice
Abstract : The aim of this study is to develop a model to analyze the macroeconomic effects of two dimensions of inequality – gender inequality and functional income distribution – and public spending, in particular on social infrastructure, on output, productivity, and hours of employment of men and women. This study estimates the model econometrically using an IV-GMM estimator and time series data for the period of 1970–2016 for the UK. For the estimation of productivity, the article uses IV-GMM estimations based on panel data for eighteen industries for the period of 1970–2015. The study finds that output in the UK is both gender equality-led and wage-led, and hence generally equality-led. Public social infrastructure investment has a high positive effect on both output and employment. Despite a strong positive effect on productivity, the employment of both men and women increases in the medium run. HIGHLIGHTS Output in the UK is gender equality-led and wage-led; hence the UK is equality-led. An upward convergence in wages by closing gender pay gaps leads to higher output. Public social infrastructure spending has a positive effect on output and productivity. Public social infrastructure leads to higher employment for both men and women. A mix of labor market and fiscal policies can achieve both equality and employment.